A study of metallurgical simulations and mechanical analyses for casting valve products through OPEX approach - Özkan, Erhan (İdris Karagöz, 2025)
In this study, information about the improvement of metallurgical simulations for the processes, and mechanical analyses for the designs of valves, which are generally preferred made of bronze in marine industry and thought to not be able to be improved much anymore, was shared with the operational excellence (OPEX) approach. The two-dimensional (2D) designs of the products to be analysed were made in AutoCAD, and the three-dimensional (3D) designs were made by using design and solid modelling program (Solidworks). Mechanical analyses for determining the mechanical strength of the specimens were performed with the help of finite element analysis (FEA) method by using the ANSYS software. The definition of the fluid resistance and flow coefficients were carried out by using computational fluid dynamics (CFD) with the help of ANSYS fluid option. The casting stages’ simulations were carried out to define filling time, change in temperature, internal stresses, which causing micro and macro shrinkages, and solidification mechanism by using Anycasting. Simufact Forming simulation program was used for defining the parameters of disc material production by hot forging method. Minitab data analysis program was selected to provide a correlation in the torque value between the disc and the body. The total consumed energy and carbon footprint was determined by using Solidworks sustainability report. Cast body weight and production time was improved 19.46% and 26.67% respectively, and hot forged valve core disc were produced with zero defect by OPEX approach. 31.87% energy savings with a total energy consumption, and 26.05% carbon footprint improvement was achieved in existing products. Finally, 81.50% improvement in the flow coefficient and 204.89% improvement in fluid resistance coefficient has been obtained as an excellence part of this study.

Bu çalışmada, denizcilik sektöründe yaygın olarak bronzdan yapılan ve artık fazla geliştirilemeyeceği düşünülen vanaların tasarımlarına yönelik mekanik analizler ve proseslere yönelik metalurjik simülasyonların iyileştirilmesi hakkında bilgiler operasyonel mükemmellik (OPEX) yaklaşımı ele alınarak paylaşılmıştır. Analizi yapılacak ürünlerin iki boyutlu (2D) tasarımları AutoCAD programında, üç boyutlu (3D) tasarımları ise tasarım ve katı modelleme programı (Solidworks) kullanılarak yapılmıştır. Numunelerin mekanik dayanımlarının belirlenmesine yönelik mekanik analizler, ANSYS yazılımı kullanılarak sonlu elemanlar analizi (FEA) yöntemi yardımıyla gerçekleştirilmiştir. Akışkan direnci ve akış katsayılarının tanımı, ANSYS akışkan seçeneği yardımıyla hesaplamalı akışkanlar dinamiği (CFD) kullanılarak yapılmıştır. Anycasting kullanılarak dolum süresi, sıcaklık değişimi, mikro ve makro büzülmeye neden olan iç gerilmeler ve katılaşma mekanizmasının tanımlanması amacıyla döküm aşamalarının simülasyonları gerçekleştirilmiştir. Sıcak dövme yöntemiyle disk malzeme üretim parametrelerinin tanımlanması için Simufact Forming simülasyon programı kullanılmıştır. Minitab veri analiz programı, disk ile gövde arasındaki tork değerinde korelasyon sağlamak üzere seçilmiştir. Toplam tüketilen enerji ve karbon ayak izi Solidworks sürdürülebilirlik raporu kullanılarak belirlenmiştir. Çalışma neticesinde döküm gövde ağırlığı ve üretim süresi sırasıyla %19,46 ve %26,67 iyileştirildi ve OPEX yaklaşımıyla sıcak dövme valf göbeği diski sıfır hatayla üretildi. Toplam enerji tüketiminde %31,87 enerji tasarrufu, mevcut ürünlerde ise %26,05 karbon ayak izi iyileştirmesi sağlandı. Son olarak bu çalışmanın mükemmellik yaklaşımı neticesinde geliştirilen bir parçasında akış katsayısında %81,50, akışkan direnci katsayısında ise %204,89 iyileşme elde edilmiştir.
OPEX yaklaşımı yoluyla döküm vana ürünleri İçin metalurjik simülasyonlar ve mekanik analizler üzerine bir çalışma
Keywords: Computational Material Sciences; Hesaplamalı Malzeme Bilimleri